Preparation of large-area ultrathin carbon semiconductors converted from conjugated microporous polymer films. Issue 30 (3rd June 2019) - Ju, Shang; Ding, Yamei; Yin, Yuhang; Cheng, Shuai; Wang, Xiangjing; Mao, Huiwu; Zhou, Zhe; Song, Mengya; Chang, Qing; Ban, Chaoyi; Liu, Zhengdong; Liu, Juqing
Abstract : Large-area carbon semiconductors were prepared by combining the in situ polymerization with thermal annealing process. Moreover, a photodetector based on carbon dots decorated carbon semiconductors was fabricated. Abstract : Two-dimensional carbon semiconductors have aroused great attention due to their unique structures and novel properties, showing potential applications in emerging electronic and optoelectronic devices. In this work, we reported an effective strategy to controllable prepare ultrathin carbon nanofilms (CNFs) by combining in situ -growth and stepwise thermal annealing, with the features of large-area, tunable properties and nanoscale thickness. The structures, morphologies and electrical properties of these as-prepared CNFs were characterized systematically. Impressively, tunable electrical properties from low to semi- and high conductivity could be precisely achieved through stepwise annealing of conjugated microporous polymer films. By introducing CNF-750 as the active channel layer, the transistor exhibited a typical p-type semiconductor property. Moreover, by further coupling CNF-750 with carbon dots (CDs) as a photoresponse layer, the as-fabricated all-carbon diode based on CDs/CNF-750 heterostructure film showed high ultraviolet (UV) light response.